Multimorbidity and Physical and Cognitive Function: Performance of a New Multimorbidity-Weighted Index - Wei, Melissa Y (J Gerontol A Biol Sci Med Sci, 2018)
BACKGROUND: Multimorbidity is an important health outcome but is difficult to quantify. We recently developed a multimorbidity-weighted index (MWI) and herein assess its performance in an independent nationally-representative cohort. METHODS: Health and Retirement Study (HRS) participants completed an interview on physician-diagnosed chronic conditions and physical functioning. We determined the relationship of chronic conditions on physical functioning and validated these weights with the original, independently-derived MWI. We then determined the association between MWI with physical functioning, grip strength, gait speed, basic and instrumental activities of daily living (ADL/IADL) limitations, and the modified Telephone Interview for Cognitive Status (TICS-m) in adjusted models. RESULTS: Among 20,509 adults, associations between chronic conditions and physical functioning varied several-fold. MWI values based on weightings in the HRS and original cohorts correlated strongly (Pearson’s r = .92) and had high classification agreement (κ statistic = .80, p < .0001). Participants in the highest versus lowest MWI quartiles had weaker grip strength (−2.91 kg, 95% confidence interval [CI]: −3.51, −2.30), slower gait speed (−0.29 m/s, 95% CI: −0.35, −0.23), more ADL (0.79, 95% CI: 0.71, 0.87) and IADL (0.49, 95% CI: 0.44, 0.55) limitations, and lower TICS-m (−0.59, 95% CI: −0.77, −0.41) (all p < .001). We observed monotonic graded relationships for all outcomes with increasing MWI quartiles. CONCLUSION: A multimorbidity index weighted to physical functioning performed nearly identically in a nationally-representative cohort as it did in its development cohorts, confirming broad generalizability. MWI was strongly associated with subjective and objective physical and cognitive performance. Thus, MWI serves as a valid patient-centered measure of multimorbidity, an important construct in research and clinical practice.